PROPOSAL NUCLEAR NAVAL PROPULSION DARI INDONESIA UNTUK PBB SEBAGAI RESPONS ATAS DINAMIKA KEAMANAN DI INDO-PASIFIK - Arthamevya Zherlindya Putri Darmawan; Ratu Salmazahra Karmilawaty (Department of International Relations Universitas Satya Negara Indonesia, 2023)
Australia, the United States, and the United Kingdom set up AUKUS defense technology cooperation in 2021. In this collaboration, the United States and the United Kingdom show commitments to help Australia have nuclear-powered submarines. The nuclear-powered submarine development program triggered Indonesia to submit an Indonesian paper entitled Nuclear Naval Propulsion during the Non-Proliferation Treaty conference at the United Nations headquarters in 2022. The paper contains Indonesia’s proposal to bridge countries that support AUKUS and countries that protest against AUKUS. In the Indonesian paper, Indonesia stated that the country agreed on the development of nuclear energy, but it should be for peaceful purposes, not for the development of nuclear weapons. This study aims to analyze why Indonesia proposed the Nuclear Naval Propulsion. This study uses a qualitative methodology and Graham Allison's rational actor theory to explain the advantages and disadvantages of a policy. This research found that Indonesia submitted the Indonesian paper because Indonesia saw the indecisiveness of the articles in the Non-Proliferation Treaty. Through the Indonesian paper, Indonesia seeks to maintain state sovereignty and security, fill the legal vacuum regarding nuclear powered submarines, and protect the Indonesian marine environment from the threat of nuclear weapons.